Dostopnost objektov za funkcionalno ovirane osebe - Bizjak, Igor (Urbani izziv, 2022)
The situation in Slovenia in terms of the accessibility of public buildings for functionally impaired persons is concerning. Most often people with disabilities already face barriers when accessing the building (no disabled parking available, stairs leading to the entrance into the building, thresholds that are too high, doors too heavy to open, handles set too high, etc.) and then in the building itself (staircases, unadapted lifts, insufficiently large toilets, etc.). To show potential barriers to the functionally impaired as well as the building owners and maintenance staff, a method is presented for inventorying building accessibility for the functionally impaired using online tools. The method relies on relevant universal accessibility legislation and standards, and it is important because it facilitates an accurate and comparable evaluation of potential barriers and adaptations already in place. Thus, it functions both as a multifunctional framework for evaluating the accessibility of all buildings, which provides an overview of and displays potential barriers to building owners and maintenance staff, and as a guide to building accessibility for the functionally impaired. Also presented is the method’s implementation in the online system for inventorying building accessibility, which makes it possible to monitor building accessibility for the needs of the functionally impaired and provides an overview of the barriers detected for the building owners and maintenance staff.
Keywords: accessibility inventorying method; accessibility monitoring system; functionally impaired; funkcionalno ovirane osebe; indoor accessibility; metoda za popis dostopnosti; notranja dostopnost objektov; online app; sistem spremljanja dostopnosti; spletna aplikacija; spletna orodja; web tools